Information Technology Development Risks in the Banking Sector - N. E. Sokolinskaya; L. M. Kupriyanova (Мир новой экономики, 2020)
The relevance of the article is because in parallel with the processes of introduction of innovations in the field of automation and computerization of the banking system, the number of types of banking risks associated with innovations in the field of on-line customer service and internal Bank reporting, as well as information systems. As a result of this article, we have studied the latest legislative acts of the Central Bank of Russia as a mega-regulator and summarized the practice of both individual credit institutions and the banking sector in the field of information technology development risks in the banking sector. To strengthen the development of new financial technologies in the digital economy, it is necessary to regularly discuss the emergence of new phenomena and innovations; to consider the possibility of further analysis of existing methodological developments to exchange best practices of banks. Building an effective it security risk management system is not a one-time project. Still, a complex process is important, focused on minimizing external and internal threats and taking into account the limitations on resources and time factor